2021
DOI: 10.1016/j.heliyon.2021.e08382
|View full text |Cite
|
Sign up to set email alerts
|

Status of metals in serum and urine samples of chronic kidney disease patients in a rural area of Bangladesh: An observational study

Abstract: The traditional causes of Chronic Kidney Damage (CKD) are Diabetes and Hypertension. However, recent studies reported the possible relations between metal exposure and CKD. This study aims to explore the status of metals in CKD patients compared to their healthy counterparts at Narayanganj, Bangladesh, through a cross-sectional study. In this study, 50 volunteers were involved; 30 CKD patients and 20 healthy controls. Five metals were measured from serum [Copper (Cu) and Zinc (Zn)] and urine [Lead (Pb), Cadmiu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…In that study, compared to the controls, CKD patients exhibited signi cantly higher levels of Pb, Cd and Cr levels in their urine samples. This signi es a potential association between heavy metal exposure and CKD [34]. As CKDu is an endemic disease, the results our study suggest an association of heavy metals with CKDu in the Indian population, and so the generalizability of the result should be used with caution.…”
Section: Discussionmentioning
confidence: 56%
“…In that study, compared to the controls, CKD patients exhibited signi cantly higher levels of Pb, Cd and Cr levels in their urine samples. This signi es a potential association between heavy metal exposure and CKD [34]. As CKDu is an endemic disease, the results our study suggest an association of heavy metals with CKDu in the Indian population, and so the generalizability of the result should be used with caution.…”
Section: Discussionmentioning
confidence: 56%
“…In that study, compared to the controls, CKD patients exhibited significantly higher levels of Pb, Cd, and Cr levels in their urine samples. This signifies a potential association between heavy metal co-exposure and CKD [ 29 ]. In the current study a significant correlation between blood Cd, Pb, and Cr and urine Cd, Pb, and Cr were found in CKDu and CKD subjects compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium(Cd) exposure, in particular, has been associated with severe kidney damage through the downregulation of specific microRNAs, thereby promoting apoptosis induced by cadmium and other heavy metals ( 7 ). Studies in Bangladesh have reported higher levels of lead (Pb), cadmium and chromium (Cr) in the urine of CKD patients compared to controls, suggesting a potential link between heavy metal exposure and CKD ( 8 ). However, existing research often fails to address combined exposure to multiple metals, overlooks covariance between them, and does not clarify the correlation between metal exposure and renal function parameters.…”
Section: Introductionmentioning
confidence: 99%